Prescribing patterns in patients with chronic liver and kidney disease in a tertiary care hospital - Mathema, Pratichhya; Neupane, Dinesh R.; Shrestha, Safal K. (International Journal of Research in Medical Sciences, 2024)
Background: Liver diseases are major cause of mortality and morbidity worldwide. It is the 12th leading cause of death liver diseases can be classified as acute if the onset of symptom does not exceed six months or chronic if symptoms persist beyond this period. According to the recently available World Health Organization. The aim of study is to facilitate rational use of medicines. Methods: This study is a prospective, observational, single center study which include patients aged ≥18 years, diagnosis of liver diseases with or without co-morbidities and is conducted at out-patient of Medicine department, Rajindra Medical College and Hospital, Patiala. Results: In this study, total of 97 prescriptions of patients with liver disease were analyzed. Out of 97 patients, the majority of patients were male. In ALD, males were 32 (78%) whereas female were 9 (22%) while in CLD males were 47 (84%) and females were 9 (16%).While observing the LFT profile of patients with ALD common tests were observed which includes total bilirubin (1.82±2.42), SGOT (96.81±117.49) and SGPT (94.78±142.94) and in patients with CLD common tests were observed which includes total bilirubin (2.50±3.63), SGOT (67.50±43.04), SGPT (47.10±33.12), blood urea (46.92±24.14) and alkaline phosphatase (147.02±63.14). Conclusions: The study interprets the prescribing pattern of drugs used in patients with ALD and CLD and observed that vitamins and minerals and antibiotics were the most prescribed in order to avoid further complications followed by hepatoprotective agents, antiulcer drugs, antihypertensives and laxatives.